Abnormal Gait in hemiplejia after stroke [İnmeye baǧli hemi̇pleji̇de yürüme anomali̇leri̇] - (:unkn) unknown (My University, 2005)
Stroke is defined as a nontraumatic brain injury caused by occlusion or rupture of cerebral blood vessels that results in sudden neurological deficit characterized by loss of motor control, altered sensation, cognitive or language impairment, disequilibrium or coma. Many stroke survivors require rehabilitative process and a rehabilitation center includes mainly stroke survivors in all over the world as well as in our country. Although gait abnormalities in stroke patients are well described, these anomalies change from patient to patient. Gait abnormalities in a stroke patient can be explained by primitive locomotor patterns, impaired postural responses, abnormal muscle tone, inappropriately timed muscle contractions and diminished muscle strength. Walking abnormalities in hemiplegia include a decrease in the speed of walking with a shorter duration of stance phase, a decrease in weight bearing, and an increased swing time for the involved limb. Also a decrease in single support time can be seen due to a decrease in weight bearing on the involved limb. On the other side, the unaffected limb has increased stance time. Impaired functional activities and limited daily living activities can be observed in a subject with stroke due to gait abnormalities. Therefore, it is very important to recognize the problem in order to overcome the abnormalities caused by stroke.
Keywords: Gait; Hemiplegia; Stroke